A review on dam engineering practice and sustainability in Nigeria - Ezugwu, Charles; Onyekweredike, Kelechi; Odumade, Adegboyega; Ezugwu, Chisom; Ifionu, Stephen; Oloyede, Amodu; Omunakwe, Okechukwu (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study focuses on dam structures in Nigeria, its availability, features, usefulness, benefits and costs, functionality and sustainability. The gap found in World Commission on Dams (WCD) Report on Dam Development being inability to proffer solutions to problems encountered by the downstream population was highlighted and discussed also. The procedure for this research work involved use of journals, books and other related literature. It was observed that many dam projects in Nigeria are lacking in areas of feasibility studies, design and construction procedure, operation and maintenance, which resulted to dam related problems like flooding and sometimes collapse of some dams. Downstream population rather than reaping abundant dam benefits record costs since their means of livelihood is hampered, affecting their social, environmental and economic well-being. This study observed that Nigeria has large, medium and small dams which are also single and multipurpose. Environmental Impact Assessment (EIA) is recommended for each dam project and a committee should be set-up to monitor its implementation to the later, from inception to end of the project for its sustainability. This paper recommends fresh attention to dam impacts on upstream and downstream population to enable them benefit immensely from these river valley projects.